Factors affecting the sustainability of innovation-based businessmanagement Pharmaceutical companies in Iran (Scientific Journal of Research Studies in Future Management, 2023)
Sustainability of business management is a category that is associated with the possibility of growth and success and achievement of organizational goals. Therefore, examining its context is an important and fundamental issue. It was formed on innovation. The method of this research was descriptive exploratory and its population was all employees, experts and experts in the field of business management in pharmaceutical companies. 385 people formed the research volume based on Cochran's formula by available sampling method.Findings showed that out of 32 existing effective indicators in this field, 5 main factors can be identified. These factors were named based on the opinion of experts and content analysis of the concepts of management model, operational flexibility, value-added models, digital marketing, competitive advantage. Based on the rating of the agent being measured; Respectively ; The components of operational flexibility, management model, value-creating models, competitive advantage and digital marketing have had the greatest impact on the sustainability of innovation-based business management